2021
DOI: 10.1371/journal.ppat.1010038
|View full text |Cite
|
Sign up to set email alerts
|

DNA double strand break position leads to distinct gene expression changes and regulates VSG switching pathway choice

Abstract: Antigenic variation is an immune evasion strategy used by Trypanosoma brucei that results in the periodic exchange of the surface protein coat. This process is facilitated by the movement of variant surface glycoprotein genes in or out of a specialized locus known as bloodstream form expression site by homologous recombination, facilitated by blocks of repetitive sequence known as the 70-bp repeats, that provide homology for gene conversion events. DNA double strand breaks are potent drivers of antigenic varia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…brucei population in in vitro cell culture. Prior studies employed the I- Sce I meganuclease to introduce a DNA break adjacent to the active VSG and to initiate efficient VSG switching [ 9 , 10 , 12 , 13 ]. These studies also indicated that resection from the break promoted recombination within upstream tandem 70-bp repeats, followed by VSG gene conversion (see Fig 1B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…brucei population in in vitro cell culture. Prior studies employed the I- Sce I meganuclease to introduce a DNA break adjacent to the active VSG and to initiate efficient VSG switching [ 9 , 10 , 12 , 13 ]. These studies also indicated that resection from the break promoted recombination within upstream tandem 70-bp repeats, followed by VSG gene conversion (see Fig 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…brucei cell [ 7 ]. The active VSG is transcribed in one of fourteen alternative sub-telomeric ‘bloodstream’ expression sites (ESs) in the ‘427’ strain [ 8 ] and switching is typically triggered by spontaneous DNA double-strand breaks that result in homologous recombination and gene conversion, replacing the active VSG [ 9 12 ]. In the first weeks of infection, donor VSG templates are typically from repressed ESs or from the ends of approximately 100 minichromosomes [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of experimentally-induced VSG switches have typically cloned a relatively small number of cells after induction of a DSB and allowed the clones to grow to a sufficient density before analysis. This made it impractical to study the events during or immediately after a DSB-induced switch 19,21,3436 . However, after establishing our SL-adapted version of Smart-seq3xpress, which was able to detect VSG expression in single cells with high precision and minimal background, we were able to monitor VSG expression in single cells before and at various times after induction of a DSB within VSG-2 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have proposed DNA recombination to be the predominant means of VSG switching following induction of a DSB in BES1 21,34,36 . Our data instead shows that in situ switches in VSG expression are as likely to occur as DNA recombination-based switches following a DSB in VSG-2 .…”
Section: Resultsmentioning
confidence: 99%
“…The fact that only very short stretches of homology could be found within the N-terminal domain, however, is consistent with recombination through microhomology-mediated end joining, a DNA repair mechanism that uses short stretches of homology (5 to 20 bp) to repair DNA damage ( 57 ). This appears to be the favored form of DNA repair in the VSG expression site and has been hypothesized to play a role in VSG switching ( 57 , 58 ). The data presented here suggest this mechanism, or a similar one, may play a role in diversification of the VSG repertoire as well.…”
Section: Discussionmentioning
confidence: 99%